If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22.4 = 7v Solving 22.4 = 7v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-7v' to each side of the equation. 22.4 + -7v = 7v + -7v Combine like terms: 7v + -7v = 0 22.4 + -7v = 0 Add '-22.4' to each side of the equation. 22.4 + -22.4 + -7v = 0 + -22.4 Combine like terms: 22.4 + -22.4 = 0.0 0.0 + -7v = 0 + -22.4 -7v = 0 + -22.4 Combine like terms: 0 + -22.4 = -22.4 -7v = -22.4 Divide each side by '-7'. v = 3.2 Simplifying v = 3.2
| 4(2x-5)=x+2 | | -32-4x=6(x-6)-8x | | X-2=8x | | x-4-1=-1-5x+8x | | 8x-(4x-8)=8 | | 9+2(7u-5)=-2(5u-4)+6u | | 2x+28=90 | | 8500x=.02852 | | .02852/8500 | | 90=10b-90 | | 2(3x-2)=3(2x+4) | | y=x*(x-1) | | 1+5x=-10 | | 6n-3n= | | 5p+7q=45 | | -3(7v-2)+9v=-2(v+4) | | -19u=17-18u | | x-24=25 | | 3.2k=30 | | 31-4x=7(2n+2) | | -3(3x-2)=-3x+25 | | 2x+3(-7-4x)=14-5x | | -70x^2+36x=-10 | | -13-p=6p+1 | | -5(x+2)=x-2+2(2x+2) | | 3(n-15)+8=11 | | (H^2+4h-4)+(5h^2-8h+2)=6h^2-4h-2 | | 1/4+w=6 | | ax+6=(x+3) | | 2w+2l=l | | -16x^2+8x+190=0 | | 1/4+w=61/3 |